Study-creative practice «Open-air» in system of preparation of the students on a speciality «Fine arts» (Педагогіка вищої та середньої школи, 2007)
In clause «Open-air» in conditions of introduction of elements of credit-modular system of training is stated the rough program of study-creative practice, the purpose a task is determined, is ordered the characteristics of substantial modules.